Taxpayer Efforts in the Examination Procedure to do not Continue in the Investigation Process - Alikin, Alberth Limandau; Suryawati, Nany (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The obligation to pay taxes that are compelling for the needs of state development, which is regulated based on the 1945 Constitution, in Article 23A. Purpose to find out (1). The process of examining taxpayers in decision No.19 / PIS / SUS / 2015 / Pekan Baru High Court is in accordance with applicable procedures. (20). This is to determine the legal remedies for taxpayers in the audit process so that they are not processed during investigation. The research method using juridical normative using primary law, namely: (a). KUHP, KUHAP (b). Tax laws and regulations, (c). Secondary legal materials as an explanation of primary law, namely: (1). Research form (2). Type of normative legal research (3). The process of collecting and analyzing data. Conclusion: There is an examination process for tax violations that refers to the existing laws and regulations. (1). Investigate tax violations (2). Carry out investigations guided by the provisions of the Criminal Procedure Code Keywords: Taxpayer, Examination Procedure, Investigation Process